Accelerated crystallization and encapsulation for the synthesis of water- and oxygen-resistant perovskite nanoparticles in micro-droplets. Issue 23 (5th June 2019) - Long, Zi; Wang, Yan; Fu, Qiang; Ouyang, Jin; He, Lixin; Na Na,
Abstract : Water- and oxygen-resistant perovskite nanoparticles (PC-PNPs) were synthesized in milliseconds via a single-step microdroplet reaction. Abstract : Water- and oxygen-resistant perovskite nanoparticles (PC-PNPs) were synthesized in milliseconds via a single-step microdroplet reaction. It was found through kinetics studies that the synthesis was accomplished within 100 ms in microdroplet reactors, with ejection at ∼1.5 m s −1 . Being small-sized, stable, less toxic and biocompatible, PC-PNPs were feasible for cell or in vivo imaging, and selective sensing for Fe 3+ and Cys, which will inspire further expanded studies of perovskite materials.